Cervantes A collection of critical essays - 20160731 frey50; Nelson, Lowry Jr (Prentice-Hall, Inc Englewood Cliffs, New Jersey, 1969)
Critical essays about Miguel de Cervantes and his creation, Don Quijote.
Cervantes / Gerald Brenan -- Example of Cervantes / Harry Levin -- Voyage with Don Quixote / Thomas Mann -- Ironic hero : some reflections on Don Quixote / W.H. Auden -- On the significance of Don Quijote / Leo Spitzer -- Enchanted dulcinea / Erich Auerbach -- Literature and life in Don Quixote / E.C. Riley -- Cervantes and the picaresque mode : notes on two kinds of realism / Carlos Blanco Aguinaga -- On the Interludes of Cervantes / Edwin Honig -- Ocean of story / William J. Entwistle.
Keywords: Cervantes Saavedra, Miguel de -- 1547-1616